Peran Gaya Kepemimpinan dan Budaya Organisasi dalam Meningkatkan Kinerja Karyawan melalui Kepuasan Kerja - Prasetyo, Iman; Ali, Hapzi; Rekarti, Endi (Jurnal Ilmu Manajemen Terapan, 2023)
The issues that arise in relation to employee performance are a sign that executive and administrative duties as head of HR assets are very important. If this performance problem is not handled as expected, the company in general will experience a gradual decline and be detrimental to the actual company, so it is necessary to study employee performance related to factors of leadership style, organizational culture and job satisfaction, so that the impact on performance can be known. . This study used a qualitative descriptive method and a literature review. The results of the study show that leadership style and organizational culture influence job satisfaction. Leadership style, organizational culture, and job satisfaction affect employee performance, and job satisfaction is able to mediate the influence of leadership style and organizational culture on employee performance.